Establishing the professional board for child and youth care - The next step in professionalising child and youth care - Lombard, J (Social Work/Maatskaplike Werk, 2002)
The White Paper for Social Welfare accepted by Government in 1997 contains the official principles, guidelines, recommendations, policies and programmes for developmental social welfare in South Africa. With reference to the human resources responsible for social welfare, this "road map" for social welfare in South Africa indicated inter alia that: the human resource capacity needed to be significantly expanded through the utilisation of different categories of social welfare personnel; • an accreditation system must be developed where necessary for all categories of welfare personnel, including child and youth care workers; and • the then South African Interim Council for Social Work was identified as the regulatory body concerned, with its terms of reference to be negotiated and amended if necessary (White Paper 1997: 33 and 35). After consultations with a wide variety of role players and stakeholders, the Social Work Amendment Act, 1998, came into operation on 1 April 1999 . This Act provided for the establishment of the South African Council for Social Service Professions (replacing the Interim Council) and the institution, under the auspices of the Council, of professional boards for the various social service professions.